Determinants of Village Fund Budget Discipline and its Impact on the Principles of Village Financial Management (International Forum of Researchers and Lecturers, 2025)
This study aims to empirically examine the influence of human resources (HR) and technological resources (TR) on village fund budget discipline and its subsequent impact on the principles of village financial management, which include participation, accountability, and transparency. Conducted in all hamlets of Bungo Regency, Jambi Province, this research adopts a quantitative approach with an explanatory design. Primary data were collected through questionnaires distributed to hamlet government officials. The study population comprised 141 hamlets, all of which were included as research samples using a census method to ensure comprehensive coverage. Data analysis was performed using the Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS) with the SmartPLS software. The findings reveal that both human resources and technological resources have a positive and significant effect on budget discipline. Furthermore, budget discipline itself significantly influences the principles of village financial management, specifically enhancing participation, accountability, and transparency. An important contribution of this study lies in identifying budget discipline as a mediating variable that bridges the impact of human and technological resources on the principles of village financial governance. In addition, this research introduces a new indicator in measuring budget discipline—namely, the “on target” criterion—which serves as a metric for assessing the effectiveness of village fund utilization in achieving predetermined objectives. Overall, the results highlight that budget discipline is not merely a procedural requirement but a strategic element in ensuring participatory, transparent, and accountable village financial governance. Strengthening human and technological resources can thus be seen as an essential investment for local governments aiming to optimize the management and allocation of village funds in line with good governance principles.